38.4k views
5 votes
Solve for x. If the equation is an identity write identity or if it has no solution write no solution.

3(5x−2)−6x=3(3x+2)

2 Answers

3 votes

3(5x−2)−6x=3(3x+2)


distribute


15x-6 -6x = 9x+6


combine like terms


9x-6 = 9x+6


subtract 9x from each side


-6 =6


no solution

User Todd DeLand
by
5.4k points
3 votes

3(5x−2)−6x=3(3x+2)

distribute

15x-6 -6x = 9x+6

combine like terms

9x-6 = 9x+6

subtract 9x from each side

-6 =6

no solution

User Toon Lite
by
5.3k points